Natural enemies of Varroa destructor identified from Eastern North American honey bee colonies: a biological survey of candidates for mite control from Maryland, USA - Posada-Flórez, Francisco; Sonenshine, Daniel; Evans, Jay; Boncristiani, Dawn; Pava-Ripoll, Monica; Cook, Steven (Biocontrol science and technology, 2025)
A survey was conducted of microbes and arthropods associated with Varroa destructor (Acari: Varroidae) mites (hereafter, Varroa) collected from honey bee colonies in Maryland, USA. Live Varroa were challenged with samples of both microbes and arthropods and assessed for their potential as biocontrol agents against the mites. To our knowledge, this is the first survey of natural enemies of Varroa conducted in North American honey bee colonies. The survey revealed 21 fungi, 25 bacteria, one nematode, and 8 arthropod species associated with Varroa in honey bee colonies, and from challenge assays using 11 of these, including 4 species of fungi, 2 species of bacteria, a parasitic nematode, 2 insects (Hemiptera and Hymenoptera), and 2 arachnids (Pseudoscorpiones) were capable of killing Varroa. This assemblage of Varroa natural enemies was similar to taxa identified from surveys conducted elsewhere globally, suggesting there is a core assemblage of organisms capable of killing Varroa that are best suited to tolerate the sometimes-hostile abiotic and biotic conditions of the hive environment. Generally, entomopathogenic fungi and bacteria assessed in our study showed the highest efficacy against Varroa, and for some, efficacy was comparable to that determined by other researchers, suggesting entomopathogenic fungi and bacteria appear to be the most promising candidates for development into commercially viable varroicides. A novel parasitic nematode identified from our survey killed greater than 90% of infected hosts. In addition, the behaviours of some arthropods toward Varroa observed in our study were indicative of predation on the mites.